STRATEGIC ROLES OF INFORMATION TECHNOLOGY AS ACCELERATOR IN DISTANCE LEARNING AND ON-LINE PROGRAMS - Abdullah, Halim Hilman; Ishak, Salomawati (International Business Education Journal, 2019)
Hyper competitive rivalries are undeniable in today’s business environment. It is essential for competing firms to understand and take advantage of dynamic motion of technological breakthroughs. This paper aims to describe the movement toward hypercompetition and roles of information technology in distance learning. The research find technology is the principle accelerator toward hypercompetitive rivalries in distance learning market. Successful higher learning institutions (HLIs) are always aware of all complex interactions among competing institutions, and can observe patterns of movement and response, punches and counter punches.